A key to Vietnamese Polygonaceae genera, with note on extended distribution of \(Persicaria runcinata\) in Vietnam - Tran, Thi Phuong Anh (Academia Journal of Biology, 2024)
The present work provides a taxonomic key to the genera of Polygonaceae found in Vietnam. It also reports the first occurrence of Persicaria runcinata in Lai Chau province, extending its known distribution within the country. Detailed photographic illustrations of the specimens studied accompany the findings. This extended distribution of P. runcinata could hold significant conservation implications, emphasizing the importance of further research and conservation efforts in the region.